2019
DOI: 10.1055/a-1010-5466
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on the Stability of In-Use Insulin Pens

Abstract: Background Improper storage of insulin could decrease its potency. Manufacturers recommend that in-use insulin pens should be kept at between 25–30°C, but room temperature in tropical countries often exceeds this range. This study investigates the effect of temperature on the stability of basal insulin in cartridges 28 days after opening. Methods Four different basal insulins were evaluated. Five opened pens of each insulin type were included for each of three storage conditions and 5 unopened insulin pens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…First, it was conducted under an isothermal temperature condition rather than a cyclic temperature condition, and no insulin was withdrawn during the 21 days, which would more closely resemble a natural ambient environment and real-life practice. However, Kongmalai et al 12 reported no significant difference in insulin stability between fluctuating RTs and an isothermal temperature in an incubator (37°C). Second, to test the biological activity of heated insulin in humans, the insulin in our study was incubated for only 21 days instead of the usual 4-week period of use.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…First, it was conducted under an isothermal temperature condition rather than a cyclic temperature condition, and no insulin was withdrawn during the 21 days, which would more closely resemble a natural ambient environment and real-life practice. However, Kongmalai et al 12 reported no significant difference in insulin stability between fluctuating RTs and an isothermal temperature in an incubator (37°C). Second, to test the biological activity of heated insulin in humans, the insulin in our study was incubated for only 21 days instead of the usual 4-week period of use.…”
Section: Discussionmentioning
confidence: 98%
“…This study’s in vitro and in vivo results affirm the outcome of our previous experiment, namely that basal insulin in a pen retains its potency and biological activity after being stored at temperatures as high as 37°C for 28 days. 12 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations